The Development and Group Formation of Thai Herbal Farmers into the Industrial Sector in Accordance with Policies and Development Plans for the Herbal City in Phitsanulok Province: A Case Study of the Community Enterprise in Cultivating and Processing Medicinal Herbs, Thap Yai Chiang Subdistrict, Phrom Phiram District, with the Hmong Herbal Planting Group in Nakhon Thai District - Pounpunwong, Wasan (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The objective of this research were: 1) to study the development and group formation of Thai herbal farmers into the industrial sector under the policies and development plans of the Herbal City in Phitsanulok Province and 2) to explore the similarities and differences between successful and unsuccessful areas in developing herbal cultivation in Phitsanulok Province. The research utilized a qualitative research method, employing document analysis and in-depth interviews. The interviewees were divided into three groups: 1) The government officials (6 persons), 2) The general public including farmers and local traditional doctors (5 persons), and 3) The business sector representatives including factory owners involved in herbal production and processing (3 persons). In total, 14 individuals provided information. The research tools included interview protocols and the data analysis method involved content analysis, cross-checking information and presenting data in a narrative form. The findings of the study were as follows: 1) The missions and organizational driving forces of community enterprises and agricultural networks are modern and clearly defined, both within and outside Phitsanulok Province. The strength of the agricultural network plays a crucial role in driving the development of the herbal industry, especially in terms of on-site operations. 2) The similarities and differences between successful and unsuccessful areas in developing herbal cultivation in Phitsanulok Province are complex and depend on various factors such as different prices for various types of herbs, the readiness of each cultivation area, investment costs, agricultural technology and collaboration from external organizations. The strength and weakness of the agricultural network also play a significant role. The recommendations from this research include urging both government and private sector organizations related to policies and development plans for the Thai Medicinal Herbs City in Phitsanulok Province to develop and expand the groups and networks of herbal farmers in Phitsanulok Province to other areas. This is crucial due to the anticipated growth in the herbal market in the future.